PENGARUH KETERJANGKAUAN INFORMASI, KETERSEDIAAN FASILITAS, DAN RESPONSIVITAS TERHADAP KEPUASAN MASYARAKAT PADA PELAYANAN SIM DI POLRES DHARMASRAYA - Andri Nugroho Saputro; Yulihasri Yulihasri (Pusat Riset dan Inovasi Nasional, 2022)
Responsiveness is one of the performance indicators in determining the quality of public services because responsiveness directly describes the organization's ability to carry out its mission and goals. recognizing and meeting community needs. The purpose of this study was to determine the influence of Information Affordability, Availability of Facilities, and Responsiveness to Community Satisfaction at the Dharmasraya Police SIM Service. Testing the quality of the instrument and the feasibility of the data used in this study is a validity test and a reliability test. Instrument processing using SEM-PLS is intended for causal predictive analysis in situations of high complexity and low theoretical support. The results of this study Effect of Affordability of Information has a positive but not significant effect on Community Satisfaction, Availability of Information has a positive but not significant effect on Community Satisfaction, and Responsiveness has a positive and significant effect on Community Satisfaction on SIM services at the Dharmasraya Police.